'Steeling' effects in the association between psychological resilience and cancer treatment in prostate cancer patients. Issue 1 (9th September 2020) - Sharpley, Christopher F.; Christie, David R. H.; Bitsika, Vicki
Abstract: Objective: To test the 'buffering' effect of psychological resilience (PR) upon depression in prostate cancer patients and to also investigate any effects that past or current treatment may have had upon patients' PR as a test of the 'steeling' hypothesis of past adversity upon future resilience. Methods: A total of 576 volunteer prostate cancer patients completed questionnaires about their demographic and treatment variables, and their psychological resilience and depression. Factor analysis was used to identify the underlying components of the resilience measure. Results: PR was confirmed as an inverse correlate of depression in these men. Additionally, some past and current treatments were found to be significantly associated with patients' psychological resilience in a way suggestive of 'steeling' effects. Conclusion: These data provide support for the model of PR as being influenced by past experiences of adversity and demonstrate that association for prostate cancer patients.